THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK DISCIPLINE, AND COMPENSATION ON THE PERFORMANCE OF JANITORS IN HOSPITALS - MUTI ADAM; ISMARTAYA; TINI KARTINI; INDAH PERMATA (CV KULTURA DIGITAL MEDIA, 2023)
This study aims to determine the conditions of organizational culture, work discipline, compensation and employe performance, to analyze the influence of organizational culture, work discipline and compensation on employee performance simultaneously, and to analyze the influence of organizational culture, work discipline, and compensation on performance partially on the cleaning service staff of Ciawi Hospital, Bogor Regency. The research approach uses descriptive quantitative methods. The research population was all janitors at Ciawi Hospital, Bogor Regency, which amounted to 95 people. The technique used in sampling in this study is saturade sampling. Analysis of the data using multiple correlation coefficient and analysis of the coefficient of determination. The result showed that organizational culture, work discipline, and compensation bpth simultaneously and partially had a positive and significant effect on the performance of the cleaning staff at Ciawi Hospital, Bogor Regency.